Striking the Balance: Exploring the Interplay Between Quality and Cost in Modern Production Engineering - Ranjeet Singh Jadaun; Akash Pawar (International Journal of Industrial and Product Design Engineering, 2024)
This review paper examines the intricate and evolving relationship between quality and cost in the context of modern production engineering. In today's dynamic manufacturing landscape, the pursuit of excellence in product quality necessitates a strategic alignment with cost-effective methodologies, ensuring the sustainability and competitiveness of practices. This article serves as a comprehensive synthesis of current research, methodologies, and case studies, aiming to illuminate the dynamic interplay, challenges, and strategies adopted by production engineers in their pursuit of an optimal equilibrium between quality and cost. As manufacturing processes undergo continuous evolution, the need to strike a delicate balance between achieving high-quality standards and managing production costs becomes increasingly imperative. The paper navigates through this complex terrain, drawing on existing literature to provide a nuanced understanding of the challenges inherent in this balancing act. By delving into the strategies employed by production engineers, the article seeks to offer valuable insights for practitioners and researchers alike. The dynamic interplay between quality and cost is explored through an examination of real-world case studies across diverse industries. These cases serve as illustrative examples, shedding light on successful strategies, potential pitfalls, and the multifaceted nature of the challenges faced in achieving the desired equilibrium. The analysis extends beyond historical perspectives to encompass contemporary challenges, including global competition, market demands, and the integration of emerging technologies.
Keywords: Automation; Manufacturing landscape; Quality; balancing; cost; production engineering; total quality management